1993
DOI: 10.1016/0014-5793(93)80731-9
|View full text |Cite
|
Sign up to set email alerts
|

Different ratios in 20 S proteasomes and regulatory subunit complexes in two isoforms of the 26 S proteasome purified from rabbit skeletal muscle

Abstract: A ubiq~ti~ATP-de~ndent proteinase complex (26 S proteasome) was highly pm%ied from rabbit skeletal muscle. The purified 26 S proteasome easily dissociated into a 20 S proteasome and a regulatory subunit complex on nondenat~ng PAGE. By using cleavable and non-cleavable cross-linkers, it was revealed that the 26 S proteasome exists in two isoforms: one (D complex) consists of the 20 S proteasome and the regulatory subunit complex in the ratio of one to two, while the other (C complex) exists in an equal molar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…We have previously reported that the 26s proteasome can be collected in a pellet fraction by centrifugation at I00000 g for 5 h, while the ubiquitinating enzyme system is recovered in a supernatant fraction [38,45]. Crude extracts obtained from HeLa cells, which had been previously cultured at 43°C or 45°C for 30min and subsequently at 37°C for various periods, were centrifuged at 105 000 g for 5 h. The resultant supernatant and precipitate fractions were used as the ubiquitinating enzyme system fraction and the 26s proteasome fraction, respectively, and their activities toward heat-denatured '2sI-lysozyme and multiubiquitinated, heat-denatured 'Z51-lysozyme, respectively, were assayed (Fig.…”
Section: Subcellular Distribution Of Multi-ubiquitinated Proteins In mentioning
confidence: 99%
“…We have previously reported that the 26s proteasome can be collected in a pellet fraction by centrifugation at I00000 g for 5 h, while the ubiquitinating enzyme system is recovered in a supernatant fraction [38,45]. Crude extracts obtained from HeLa cells, which had been previously cultured at 43°C or 45°C for 30min and subsequently at 37°C for various periods, were centrifuged at 105 000 g for 5 h. The resultant supernatant and precipitate fractions were used as the ubiquitinating enzyme system fraction and the 26s proteasome fraction, respectively, and their activities toward heat-denatured '2sI-lysozyme and multiubiquitinated, heat-denatured 'Z51-lysozyme, respectively, were assayed (Fig.…”
Section: Subcellular Distribution Of Multi-ubiquitinated Proteins In mentioning
confidence: 99%
“…Furthermore, proteasomes are activated during in vivo Xenopus egg activation induced by treatment with the calcium ionophore A23187 (22). The 26 S proteasome consists of at least two subunits: one is a 700-kDa proteolytic core complex called the 20 S proteasome with 28 subunits, and the other is a 700 -1000-kDa regulatory subunit complex made up of ϳ20 subunits (31)(32)(33)(34)(35)(36)(37)(38). Although there are many reports that several proteasome subunits can be phosphorylated, there is little or no direct effect on proteasome activity from these modifications (39 -42).…”
Section: Fig 4 Effects Of Protease Inhibitors and Herbimycin A On Imentioning
confidence: 99%
“…ATP-dependent degradation of poly-Ubprotein conjugates by the 26 S proteasome was measured as follows; a reaction mixture (200 PI), which contained 50 mM Tris-HCI (pH 7.8), 10 mM MgCI,, 2 mM ATP, 1 mM DTT, 0.2 pg of ['2SI]proteins (18,000 cpm) tagged with multi-Ub chains and 3 lug of the 26 S proteasome purified from rabbit skeletal muscle as described previously [35], was incubated at 37°C for 2 h, and the reaction was stopped by the addition of 25 ~1 of cold 10% bovine serum albumin and 600 ~1 of cold 10% trichloroacetic acid. After standing for more than 10 min on ice, the acid-soluble radioactivity was measured by a y-counter.…”
Section: Degradation Of Poly-uandprotein Conjugatesmentioning
confidence: 99%